If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -5)(2x + 8) = 0 Reorder the terms: (-5 + x)(2x + 8) = 0 Reorder the terms: (-5 + x)(8 + 2x) = 0 Multiply (-5 + x) * (8 + 2x) (-5(8 + 2x) + x(8 + 2x)) = 0 ((8 * -5 + 2x * -5) + x(8 + 2x)) = 0 ((-40 + -10x) + x(8 + 2x)) = 0 (-40 + -10x + (8 * x + 2x * x)) = 0 (-40 + -10x + (8x + 2x2)) = 0 Combine like terms: -10x + 8x = -2x (-40 + -2x + 2x2) = 0 Solving -40 + -2x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-20 + -1x + x2) = 0 Factor a trinomial. 2((-4 + -1x)(5 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-4, 5}
| 3(6+5y)=-2(-5+4y) | | 216x-162=18(12x-9) | | 31.2p=65.1 | | (3x-24)+2x=2x | | 6(1/2u-2/3) | | 1/2x^2-6=0 | | 7x-3(3x+17)=-37 | | 2x-2+x=x-24 | | Cot/cos=CDC | | -9x-3y=7 | | 10x+26x-10=9(4x+10) | | 3(4-6y)+7=-1 | | M/9--213=231 | | 12.1=p+2.3 | | X-(156-X)=78 | | 3x-24+2x=2x | | 38x+85=38x+78 | | x2=49/81 | | 5x+4(-3x-10)=103 | | 3/4(2x–8) | | X/-1/6=6/7 | | x^2+4x-8y+12=0 | | -5(f-929)=85 | | P+2p+3p+2=2 | | 7x+23x-4=6(5x+9) | | 18(w+25)=468 | | 4x-2(1+2x)=6 | | 3.4w=9.7 | | 34x+3y=12 | | 2x(-40)=x | | 0.8k=1.36 | | 3=w-5/4 |